Ausblicke auf die Psychiatrie - Hippius, Hanns; Hess, Benno (Springer, 1984)
H. Hippius (Hrsg.): "Ausblicke auf die Psychiatrie". Springer-Verlag, Berlin, Heidelberg, New York, Tokio 1984, 135 S., DM 19,80